Who benefitted from the PyeongChang Olympic announcement? Evidence from the South Korean stock market - Hayduck III, T. (Journal of Sports Economics, 2022)
Understanding the market effects of Olympic host announcements is popular in academic research. Contrary to prior studies, announcing PyeongChang as the 2018 host had a positive effect on South Korea's Stock Market, with conservative estimates suggesting a peak of +3.8% during the 15 trading days post announcement (an increase equivalent to $34.962 billion). The degree to which firms benefitted varied by industry and lifecycle stage. Older and lower-growth financial and information technology firms saw larger abnormal returns compared to other firms. These findings suggest that academics and investors pay greater attention to idiosyncratic price adjustments to systematic market shocks.